Salvia guidongensis sp. nov.: unraveling a critical evolutionary link in East Asian Salvia from Central China integrating morphology, phylogeny, and plastid genomics - Huang, Yan-Bo; Qi, Zhe-Chen; Feng, Jie-Ying; Ge, Bin-Jie; Huang, Cun-Zhong; Feng, Yu-Qing; Wu, Jing; Wei, Pu-Rui; Ito, Takuro; Kokubugata, Goro; Li, Pan; Wei, Yu-Kun (Frontiers in Plant Science, 2024)
Salvia L., the largest genus within the mint family, boasts an estimated 1000 species distributed globally. East Asia, particularly China, emerges as a significant hub of Salvia diversity. During recent fieldwork in Guidong County, Hunan Province, China, we identified a previously undescribed species, Salvia guidongensis. This new taxon is distinguished by its unique dual floral colors, presenting either pale purple or pale yellow within natural populations, a feature seldom observed in the East Asian lineage of Salvia. While it shares morphological affinities with members of sect. Glutinaria, it distinctly stands out due to its floral morphology, intermediate stature, and specific foliar characteristics. Phylogenetic analyses, based on plastid regions, position S. guidongensis in a distinctive clade within the East Asian lineage of Salvia, potentially bridging existing taxonomic gaps. By integrating detailed morphological observations with molecular data, we validate the status of S. guidongensis as a novel species, emphasizing its role as a pivotal link in understanding the evolutionary trajectory of Sect. Glutinaria. Furthermore, we provide insights into the plastome features of S. guidongensis and compare with its close relatives. This discovery not only enriches the taxonomic tapestry of Salvia but also offers invaluable insights into the biogeography and evolution of the genus in East Asia.